Factors affecting employee retention at bank industry in Kota Bharu, Kelantan / Nik Mohamad Dzul Wal llkram Zulkarnain and Muhamad Zul Fadzli Mohd Amran - Zulkarnain, Nik Mohamad Dzul Wal llkram; Mohd Amran, Muhamad Zul Fadzli (2018)
This chapter forms and include about introduction of the research and it provide, general explanation and overview for the entire research process. This research mainly focuses and analyses about factor affecting employee retention in bank industry at Kota Bharu, Kelantan. This chapter discusses about the background of the study, problem statement, research objectives, research questions, significance of the study, scope of the study, definition of terms, and summary of this first chapter. This chapter also can help to know the factors that may lead employee retention in organization. At the same time, this chapter also can help to identify the effective way to encourage employee retention in organization.